2018
DOI: 10.1111/jpn.13048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of live yeast (Saccharomyces cerevisiae) supplementation on rumen fermentation and metabolic profile of dairy cows in early lactation

Abstract: The study evaluated dietary supplementation with live yeast (LY) Saccharomyces cerevisiae (CNCM I‐4407, 1010 CFU/g, Actisaf; Phileo Lesaffre Animal Care, France) on rumen fermentation and serum metabolic profile in lactating dairy cows. Fifty Holstein cows received a total mixed ration with (Live Yeast Diet, LYD, n = 25) or without (Control Diet, CD, n = 25) 5 × 1010 CFU/cow/day of LY from 3 to 19 weeks of lactation. Rumen fermentation and serum metabolic profile were measured in eight cows per treatment at 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
7
27
1
Order By: Relevance
“…In the present study, the tendency for a higher acetate level in cows fed LY is in agreement with results of some previous studies [33,37]. Although ruminal pH was unchanged in both groups in the current study, this situation may have been the result of higher fiber digestibility resulting from the higher level of activity of fibrolytic bacteria [38].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the tendency for a higher acetate level in cows fed LY is in agreement with results of some previous studies [33,37]. Although ruminal pH was unchanged in both groups in the current study, this situation may have been the result of higher fiber digestibility resulting from the higher level of activity of fibrolytic bacteria [38].…”
Section: Discussionsupporting
confidence: 93%
“…Although the milk yield improved, milk composition did not change in this study. Kumprechtova et al [33] also stated that milk composition was not altered by LY administration. Likewise, from their metaanalysis, Desnoyers et al [28] reported that yeast use had no effect on milk composition.…”
Section: Discussionmentioning
confidence: 96%
“…Flavonoids have been widely investigated and increasingly used in monogastric species and ruminant production systems, and have improved growth performance, health, and rumen fermentation conditions [24]. Some previous studies have reported that yeast is an effective alternative to antibiotics in ruminants [25,26], but these trials reported little benefit to calf performance [27,28]. Similar to the results of our present study, oral administration of C. tropicalis did not improve DM intake or ADG of calves [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S. cerevisiae is not directly related to aerobic spoilage through microbial analyses [6,20]. These studies have shown the possibility of using S. cerevisiae as an inoculant at the dose of 10 3 to 10 5 cfu/g, but the application dose adopted in the literature and the resultant viable cell counts are below the dose suggested to elicit a positive response in the rumen [18,21]. The effect of an increased dose of S. cerevisiae on nutrient preservation, fermentation traits and aerobic stability remains unclear and needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%